2003
DOI: 10.1093/jxb/erg070
|View full text |Cite
|
Sign up to set email alerts
|

In vitro distribution and characterization of membrane-associated PLD and PI-PLC in Brassica napus

Abstract: Two types of phospholipid degrading enzyme, phospholipase D (PLD; EC 3.1.4.4) and phosphatidyl- inositol-specific phospholipase C (PIP(2)-PLC; PI-PLC 3.1.4.11) were studied during the development of seeds and plants of Brassica napus. PLD exhibits two types of activity; polyphosphoinositide-requiring (PIP(2)-dependent PLD) and polyphosphoinositide-independent requiring millimolar concentrations of calcium (PLDalpha). Significantly different patterns of activity profiles were found for soluble and membrane-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In contrast to Kusner et al. (2003), who used recombinant Arabidopsis PLDβ1 or a crude enzymatic preparation (commercial PLD from Brassica oleracea ), we utilized a purified plasma membrane (PM) fraction for in vitro measurements of distinct PLD activities (Novotná et al. , 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Kusner et al. (2003), who used recombinant Arabidopsis PLDβ1 or a crude enzymatic preparation (commercial PLD from Brassica oleracea ), we utilized a purified plasma membrane (PM) fraction for in vitro measurements of distinct PLD activities (Novotná et al. , 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The enriched plasma membrane fraction was prepared from a tobacco cell suspension culture by partitioning microsomes in an aqueous dextran/polyethylene glycol two‐phase system (Novotná et al. , 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Cytosolic, microsomal and plasma membrane‐enriched fractions were prepared as described by Novotná et al. (2003).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been demonstrated that PIs can be targeted though vesicle trafficking to different locations throughout the cell (Kim et al, 2001), opening up the possibility that localization provides a means for discrimination between PLC/DGK and PLD signaling. Indeed, in developing Brassica napus seeds, PLC and PLD activities have been shown to differ in subcellular location (Novotna et al, 2003b). Studies on PA receptors that have been identified in plants to date have shed little light on how PA interacts with the receptors or to what extent structure or location are important for discrimination between different intracellular sources of PA (Testerink and Munnik, 2005).…”
Section: Cellular Functions Of Plcmentioning
confidence: 99%